Etiology of the orange spot disease on cladodes of dragon fruit [hylocereus undatus (haworth) britton and rose] - Deiparine, Karen Louise K. (2009)
Thielaviopsis sp. was consistently isolated from dragon fruit cladodes [Hylocereus undatus (Haworth). Britton and Rose] infected with orange spots bordered by yellow halo. Reisolation of the causal organism from inoculated cladodes confirmed the association of the fungus with the disease. The reisolated cultures have dense, white, filamentous mycelia that turn black after a few days. Under microscopy, its hyphae, which measure 59.18 (22.25) m long and 9.61 (1.48) m wide, are septated, thick-walled, hyaline, long and narrow to broad. It produces two types of conidia: 1) hyaline, cylindrical endoconidia measuring 9.40 (2.08) m long and 4.35 (1.25) m wide; and 2) pigmented, catenulate, subrectangular to circular aleurioconidia measuring 9.53 (1.89) m long and 6.1 (1.06) m wide. Colony growth and spore production of Thielaviopsis sp. in vitro were affected by several factors. Light was a key stimulator on the mycelial growth and spore production of Thielaviopsis sp. Colony growth was profused at pH 5.62 than on pH 6.62 and 7.62, but no differences on the three pH regimes were noted in terms of spore yield. Thielaviopsis sp. also preferred a higher temperature set-up (room temperature) than under a daytime air-conditioned environment mainly because its host normally lives in tropical and subtropical environments where temperatures are relatively high. An assay of various fungicides revealed that the growth of Thielaviopsis sp. was successfully inhibited by mancozeb event at concentrations below its generally recommended rates